Design and development of efficient algorithm for mobile ad hoc networks using cache. (25th May 2011) - Varaprasad, G.; Murthy G, Shiva; Jose, Johny; D'Souza, R.J.
Mobile ad hoc network is a collection of mobile nodes that can be dynamically setup anywhere anytime without having pre-existing infrastructure. This paper proposes a new routing algorithm for mobile ad hoc networks, which reduces the usage of the resource while forwarding the data packets from the source to destination with the help of support node. In order to route the data packets, the proposed model uses the tree-based cache model to increase the network throughput. It reduces the number of control message packets and average path-length in the network. The proposed model has been simulated using network simulator (NS-2.33) and has compared with AODV, DSR and DSDV models. The proposed model has shown better results in terms of packet delivery, average path-length and control message packets. The proposed model delivers 82% of the data packets when the mobility is 20 m/sec. If the mobility is 2.5-20 m/sec, then the path-length of the proposed model is 2.2-2.8 whereas DSDV model has 2.1-4, DSR model needs 3.32-3.8 and AODV model with 3.3-3.8.